Genetic diversity, seed size associations and population structure of a core collection of common beans (Phaseolus vulgaris L.) - Blair, Matthew W.; Díaz, Lucy Milena; Buendía Castellanos, Hector F.; Duque E., Myriam Cristina (Springer, 2009)
Cultivated common bean germplasm is especially diverse due to the parallel domestication of two genepools in the Mesoamerican and Andean centers of diversity and introgression between these gene pools. Classification into morphological races has helped to provide a framework for utilization of this cultivated germplasm. Meanwhile, core collections along with molecular markers are useful tools for organizing and analyzing representative sets of these genotypes. In this study, we evaluated 604 accessions from the CIAT core germplasm collection representing wide genetic variability from both primary and secondary centers of diversity with a newly developed, fluorescent microsatellite marker set of 36 genomic and gene-based SSRs to determine molecular diversity and with seed protein analysis to determine phaseolin alleles. The entire collection could be divided into two genepools and five predominant races with the division between the Mesoamerica race and the Durango–Jalisco group showing strong support within the Mesoamerican genepool and the Nueva Granada and Peru races showing less diversity overall and some between-group admixture within the Andean genepool. The Chile race could not be distinguished within the Andean genepool but there was support for the Guatemala race within the Mesoamerican genepool and this race was unique in its high level of diversity and distance from other Mesoamerican races. Based on this population structure, significant associations were found between SSR loci and seed size characteristics, some on the same linkage group as the phaseolin locus, which previously had been associated with seed size, or in other regions of the genome. In conclusion, this study has shown that common bean has very significant population structure that can help guide the construction of genetic crosses that maximize diversity as well as serving as a basis for additional association studies.